Persuasive Complex as a Unit of Analysis of Parliamentary Discourse - S. A. Gromyko (Научный диалог)
The method of analysis of speech impact in the parliamentary discourse is considered. The relevance and novelty of the research is seen in the fact that parliamentary discourse is viewed as a persuasive discourse. A methodology for analyzing the persuasiveness of this discourse is pro-posed. The category “persuasive complex” is introduced into scientific circulation, which is considered as a set of tools and methods for realizing persuasiveness, formed in a single discourse and united by a semantic unit — an image or a symbol. Using the material of the discussion of the First State Duma of the Russian Empire, the author dwells in detail on the analysis of the persuasive complex “BLOOD”. The procedure for analyzing this persuasive complex is described. The author comes to the conclusion that the persuasive complex is implemented at three levels: semantic, instrumental and operational. It is shown that representatives of all factions in the first Russian parliament actively used the “BLOOD” persuasive complex, but the options for its implementation in specific persons differed significantly. It is concluded that the persuasive complex is a unit of discourse analysis, which is aimed at identifying the semantic, formal and functional components of the addressee's impact on the recipient.